Food for Thought: The Socioeconomic Impact of Child Malnutrition and Maternal Health on the Academic Performance of Filipino School Children - Dominguez, Vashti Alexandra H.; Halili, Bernadette Louise B. (European Journal of Sustainable Development, 2018)
The study intends to investigate the effects of child malnutrition and maternal health on academic performance of Filipino school children. Previous research has shown correlation while no studies have proven causality, and so the study aims to fill the gap. Academic performance is defined as educational attainment and cognitive development. For health variables, child malnutrition is represented by prevalence of wasting in children under age 5 and maternal health is demonstrated as the percentage of pregnant women receiving prenatal care. Income, as annual GDP growth, and government expenditure on health and on education are also examined as economic variables. A multiple linear regression estimation model, based mainly on Christopher Ruhm’s economic model on child outcomes, showed that maternal health had a significant impact on cognitive development while malnutrition was significant to educational attainment, whereas the most significant economic variable was government expenditure on education. The researchers therefore recommended a focus on government policy with respect to accessible prenatal care for mothers and proper nutrition for children. Keywords: health economics, development economics, child malnutrition, maternal health, academic performance, cognitive development, educational attainment, wasting, prenatal care